Bridging Socio-Constructivism and Digital Literacy in English Speaking Instruction: Insights from North Sumatra Contents - Hassan, Muhammad; Suprayetno, Edi (Cv. Kayaswara, Indonesia, 2025)
This study investigates the integration of socio-constructivism and digital literacy principles in English speaking instruction within higher education contexts in North Sumatera, Indonesia. Responding to persistent challenges in students’ oral proficiency, confidence, and access to authentic communication, the research aimed to design, implement, and evaluate digital pedagogy practices that enhance speaking competence through collaborative, technology-mediated learning. Employing a convergent mixed-methods design, the study involved 120 English education students and 12 lecturers from three universities. Data were gathered through questionnaires, classroom observations, speaking performance assessments, and interviews, and analyzed using both statistical and thematic procedures. Findings reveal that digital storytelling, podcast-based tasks, and collaborative multimedia projects significantly improved learners’ fluency, motivation, and self-efficacy, aligning with socio-constructivist principles of interaction, scaffolding, and learner autonomy. Lecturers demonstrated increasing digital pedagogical competence but reported ongoing challenges related to infrastructure and training. The study concludes that embedding socio-constructivist approaches within digitally rich environments fosters communicative, multimodal, and culturally relevant speaking instruction. The proposed framework offers a sustainable model for integrating technology into English language teaching across comparable educational contexts.